Protective effect of vitamin D3 and erythropoietin on renal ischemia/reperfusion-induced liver and kidney damage in rats - Mohammad-ghasem Golmohammadi; Reza Ajam; Ali Shahbazi; Mir Mehdi Chinifroush-Asl; Shokofeh Banaei (Shahrekord University of Medical Sciences, 2020)
Introduction: Renal ischemia reperfusion (IR) contributes to the development of acute renal failure (ARF). Free radicals are considered to be principal components involved in the pathophysiological alterations observed during IR. In this study, we evaluated the effects of vitamin D and erythropoietin (EPO) in IR-induced renal and liver damage. Methods: Wistar rats were divided into five groups of 6 each. 1) The control, 2) IR, 3) VD3 (1,25-dihydroxyvitamin D3) + IR, 4) EPO+ IR, and 5) VD3+EPO+ IR groups. The rats were unilaterally nephrectomized and subjected to 45 minutes of renal pedicle occlusion followed by 24 h reperfusion. Vitamin D (10 mg/kg, IP) and EPO (1000 U/kg, IP) were administered prior to ischemia. After 24 hours reperfusion, the blood samples were collected for the determination of biochemical parameters and kidney and liver samples were taken for histological studies. Results: Renal ischemia significantly decreased kidney and liver functions. IR significantly increased blood urea nitrogen-creatinine (BUN-Cr), glucose, total protein and liver enzyme levels and significantly decreased hemoglobin (Hb) and hematocrit (Hct) values. Histopathological findings of the IR group confirmed that there were glomerular atrophy and acute tubular necrosis in the renal tissues and lymphocyte infiltration in the liver samples. Treatment with vitamin D and EPO boosted liver and kidney functions and improved the morphological changes. Conclusion: It seems that vitamin D or EPO administration could protect the kidney and liver damage induced by IR. Also, the combination of vitamin D and EPO may exert more beneficial effects than either agent used alone.